Menganalisis Performa Bahan Bakar Pertamax Dengan Pertalite Ditambah Zat Aditif Octane Pada Motor Honda Supra 125 CC - Pambudhi, Prastyo Alym; Kusbandono, Hermanu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Fuel is a liquid used in motorized vehicles. The aim of this research is to determine the difference in motorbike performance using Pertalite and Pertamax mixed with eco racing. Then the engine speed variations were given treatment starting from rpm 4800, 5000, 5200, 5300, 5400, 5500, 6500, 6700, 7000, 7100, 7500, 8000, 8500, 9000, 9500. The results showed that the octane value at 5300 rpm for torque the highest is 11.17 Nm (pertalite booster), the highest power at 6700 rpm is 9.36 kW